Application of a Combined Computational Grid in the Problem of Body Inhomogeneity Restoration by Near-Field Measurements - Zaytsev, B. A.; Medvedik, M. Yu (Journal of experimental and theoretical physics, 2024)
The purpose of this study is to develop an effective noninvasive method for determining the properties of an object. To this end, the inverse diffraction problem is solved using combined or generalized computational grids. In this paper, both the direct and inverse problems are described. The result of solving the direct problem follows from the solution of the corresponding volume integral equation. The inverse problem is solved using a two-step method. A numerical method is described in detail. Numerical results have been obtained, and solutions to the problems with noisy and noise-free input data have been compared.